Ephesos metropolis of Asia : an interdisciplinary approach to its archaelogy, religion and culture - Koester, Helmut, 1926-; Harvard Divinity School; Harvard University. Dept of Fine Arts.; Harvard University. Dept of the Classics (Valley Forge, PA : Trinity Press International, 1995)
This volume brings together studies of Ephesos - a major city in the Greco-Roman period and a primary center for the spread of Christianity into the Western world - by an international array of scholars from the fields of classics, fine arts, history of religion, New Testament, ancient Christianity, and archaeology.
The city of Ephesos from the Roman period to late antiquity / Peter Scherrer -- Urban development and social change in imperial Ephesos / L. Michael White -- At home in the city of Artemis: religion in Ephesos in the literary imagination of the Roman period / Christine Thomas -- Ephesos in early Christian literature / Helmut Koester -- Via Sacra Ephesiaca: new aspects of the cult of Artemis Ephesia / Dieter Knibbe -- The processional way in Ephesos as a place of cult and burial / Hilke Thür -- Preliminary views of the Ephesian harbor / Heinrich Zabehlicky -- Subsidiary factories of Italian sigillata potters: the Ephesian evidence / Susanne Zabehlicky-Scheffenegger -- The cult of the Roman emperors in Ephesos: temple wardens, city titles, and the interpretation of the Revelation of John / Steven Friesen -- Sculptures of gods and heroes from Ephesos / Maria Aurenhammer -- Egyptian religions in Ephesos / James Walters -- The church of Mary and the temple of Hadrian Olympios / Stefan Karwiese -- The Council of Ephesos: the demise of the See of Ephesos and the rise of the cult of the Theotokos / Vasiliki Limberis.
Includes most of the papers presented at a symposium organized by Harvard Divinity School and cosposored by the Harvard University Departments of Classics and Fine Arts, March 1994.
Map on folded leaf inserted at end.
Includes bibliographical references and index.
Keywords: Ephesus (extinct city) -- civilisation -- congresses; Excavations (archaeology) -- Turkey -- Ephesus (extinct city) -- congresses; Ephesus (extinct city) -- religion -- congresses; Rome -- religion -- congresses